Physical map and dynamics of the chaperone network in Escherichia coli - Kumar, Mohit; Sourjik, Victor (Molecular microbiology, 2012)
Diverse families of molecular chaperones cooperate to effect protein homeostasis, but the extent and dynamics of direct interactions among chaperone systems within cells remain little studied. Here we used fluorescence resonance energy transfer to systematically map the network of pairwise interactions among the major Escherichia coli chaperones. We demonstrate that in most cases functional cooperation between chaperones within and across families involves physical complex formation, which pre-exists even in the absence of folding substrates. The observed connectivity of the overall chaperone network confirms its partitioning into sub-networks that are responsible for de novo protein folding and maturation and for refolding/disaggregation of misfolded proteins, respectively, and are linked by the Hsp70 system. We further followed heat-induced changes in the cellular chaperone network, revealing two distinct pathways that process heat-denatured substrates. Our data suggest that protein folding within cells relies on highly ordered and direct channelling of substrates between chaperone systems and provide a comprehensive view of the underlying interactions and of their dynamics.